Chemical and Pharmacological Aspects of Caffeic Acid and Its Activity in Hepatocarcinoma - Espíndola, Kaio Murilo Monteiro; Ferreira, Roseane Guimarães; Narvaez, Luis Eduardo Mosquera; Silva Rosario, Amanda Caroline Rocha; da Silva, Agnes Hanna Machado; Silva, Ana Gabrielle Bispo; Vieira, Ana Paula Oliveira; Monteiro, Marta Chagas (Frontiers in oncology, 2019)
Caffeic acid (CA) is a phenolic compound synthesized by all plant species and is present in foods such as coffee, wine, tea, and popular medicines such as propolis. This phenolic acid and its derivatives have antioxidant, anti-inflammatory and anticarcinogenic activity. and studies have demonstrated the anticarcinogenic activity of this compound against an important type of cancer, hepatocarcinoma (HCC), considered to be of high incidence, highly aggressive and causing considerable mortality across the world. The anticancer properties of CA are associated with its antioxidant and pro-oxidant capacity, attributed to its chemical structure that has free phenolic hydroxyls, the number and position of OH in the catechol group and the double bond in the carbonic chain. Pharmacokinetic studies indicate that this compound is hydrolyzed by the microflora of colonies and metabolized mainly in the intestinal mucosa through phase II enzymes, submitted to conjugation and methylation processes, forming sulphated, glucuronic and/or methylated conjugates by the action of sulfotransferases, UDP-glucotransferases, and o-methyltransferases, respectively. The transmembrane flux of CA in intestinal cells occurs through active transport mediated by monocarboxylic acid carriers. CA can act by preventing the production of ROS (reactive oxygen species), inducing DNA oxidation of cancer cells, as well as reducing tumor cell angiogenesis, blocking STATS (transcription factor and signal translation 3) and suppression of MMP2 and MMP-9 (collagen IV metalloproteases). Thus, this review provides an overview of the chemical and pharmacological parameters of CA and its derivatives, demonstrating its mechanism of action and pharmacokinetic aspects, as well as a critical analysis of its action in the fight against hepatocarcinoma.